Cane toads : a tale of sugar, politics and flawed science - Turvey, Nigel D, 1948- (Animal publics (Series), 2013)
Cane Toads is about good intentions, unintended consequences and of simple acts leading to catastrophic outcomes. It is about scientists so committed to solving a problem, serving their country, their leaders and the industry that employed them, that they are blinkered to adverse impacts.